Efficacy of Motivational Interviewing to Enhance Advance Directive Completion in Latinos With Chronic Illness: A Randomized Controlled Trial. (November 2019) - Nedjat-Haiem, Frances R.; Cadet, Tamara J.; Amatya, Anup; Thompson, Beti; Mishra, Shiraz I.
Background: End-of-life (EOL) care for Latinos with chronic illness is a critically important problem. Latinos with chronic illness suffer worse health outcomes and poorer quality of care due to various issues occurring in care delivery systems. Latinos are less likely than non-Hispanic whites to prepare an advance directive (AD) for health-care decision-making that impacts treatment decisions for when EOL is near. Advance care planning (ACP) interventions tailored specifically for Latinos have rarely been implemented. Objective: The primary aim examines whether a motivational interviewing (MI) intervention increased rates of AD documentation among older Latinos. The secondary aim was to examine whether MI improved communication with providers and family members. Methods: We pilot tested a randomized controlled trial with older Latinos >50 years with one or more chronic illnesses, including cancer. Participants were randomly assigned to usual care (UC) receiving ACP education alone versus treatment (TX), which received ACP education, plus MI counseling including interactive decisional support, emotional support, and barrier navigation. Results: Results of logistic regression indicate TX group participants were significantly more likely to document an AD than UC, however were less ready to talk with health-care providers or family members. Those reporting navigational barriers for talking about dying is difficult showed a significant negative relationship for AD completion even with significant intervention effects. Conclusion: When using MI to motivate individuals toward ACP EOL conversations other factors are important to consider. Further research is needed, especially among Latinos to understand best practices for ACP education and counseling for EOL care.